A Quantitative Evaluation of Customer Relationship Management in a Public Complaint Service Website Using System Usability Scale (SUS) - Rakhman, M. Nugrahadi; Purnamasari, Yeni; Gismara, Rio; Nurhayati, Nurhayati; Hasibuan, M. Said (Puslitbang Akademi Relawan TIK Indonesia, 2025)
The implementation of digital transformation in public services encourages the government to provide more efficient and accessible services for the public. This study aims to evaluate user experience on the Public Complaint Service Website of the South Lampung Public Service Mall using the System Usability Scale (SUS) and analyze it within the framework of Customer Relationship Management (CRM). A quantitative descriptive approach was used, with data collected through SUS questionnaires completed by 12 respondents. The results indicate that the average SUS score is 72.5, which suggests good system usability, although there is variation in individual scores. Several issues were identified, including the complaint form filling process, the need for follow-up notifications, and the utilization of complaint data for performance analysis. The study concludes that although the system is effective, improvements in areas such as ease of use and transparency of follow-up actions are needed to enhance user satisfaction and strengthen the relationship between the government and the public. The implications of this study highlight the importance of improving CRM management to create more responsive complaint services. Limitations of this study include the limited number of respondents and the use of SUS, which only provides a general overview of usability.